Protein kinase C‐β‐dependent changes in the glucose metabolism of bone marrow stromal cells of chronic lymphocytic leukemia. (17th February 2021) - von Heydebrand, Franziska; Fuchs, Maximilian; Kunz, Meik; Voelkl, Simon; Kremer, Anita N.; Oostendorp, Robert A. J.; Wilke, Jochen; Leitges, Michael; Egle, Alexander; Mackensen, Andreas; Lutzny‐Geier, Gloria
Abstract: Survival of chronic lymphocytic leukemia (CLL) cells critically depends on the support of an adapted and therefore appropriate tumor microenvironment. Increasing evidence suggests that B‐cell receptor‐associated kinases such as protein kinase C‐β (PKCβ) or Lyn kinase are essential for the formation of a microenvironment supporting leukemic growth. Here, we describe the impact of PKCβ on the glucose metabolism in bone marrow stromal cells (BMSC) upon CLL contact. BMSC get activated by CLL contact expressing stromal PKCβ that diminishes mitochondrial stress and apoptosis in CLL cells by stimulating glucose uptake. In BMSC, the upregulation of PKCβ results in increased mitochondrial depolarization and leads to a metabolic switch toward oxidative phosphorylation. In addition, PKCβ‐deficient BMSC regulates the expression of Hnf1 promoting stromal insulin signaling after CLL contact. Our data suggest that targeting PKCβ and the glucose metabolism of the leukemic niche could be a potential therapeutic strategy to overcome stroma‐mediated drug resistance. Abstract : Protein kinase‐C‐β‐dependent changes in the metabolism of bone marrow stromal cells after contact to malignant B‐cells.